Engineering Application of Laplace Transform - Prof. Nita K.Choukade; Prof. Amit P. Mangalekar , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Basically Laplace Transform will convert function in some domain into a function in another domain, without changing value of the function. In This paper will discuss the various applications of Laplace Transform in different engineering fields. As well as it discuss about, how to solve differential equations by using Laplace Transform, How to find transfer function (T.F.) of mechanical system, How to use Laplace Transform in Nuclear Physics as well as Automation Engineering, Control Engineering and Signal processing.